Exploring the strengths and adaptations of African women refugees displaced in inner city Johannesburg - Naicker, Pravilla (My University, 2016)
A relatively large number of refugees from various African countries are currently residing in South Africa. Many of the people in this refugee population are women. This exploratory qualitative study investigated the strengths and adaptations of refugee women as well as the specific coping mechanisms that they employed. Ten voluntary participants were interviewed from the Bienvenu Shelter in Johannesburg. One-hour interviews were scheduled with each participant. The data was collected using a semi-structured interview schedule, which was designed to explore refugee experiences in Johannesburg. The interview focused particularly on the challenges that they faced and the mechanisms used to cope with their circumstances. The findings of the study pointed to the resourceful nature of women refugees with regard to their coping and adaptation mechanisms. These included mechanisms such as being able to generate an income through informal trading, creating adequate support structures to provide them with a sense of identity and the development of new skills that created more opportunities to find work. However, the study also found that the women also experienced various challenges such as the acquisition of documentation and securing employment in the inner city. The findings revealed that despite the immense challenges faced by the participants, many of them were able to cope with the demands of everyday life by utilising resources such as NGO’s and other social networks. While some of the participants were faced with much adversity upon arrival into the inner city, they now had a more positive view of life for themselves and their families. However, it was also noted that the reverse had occurred for other participants, where they initially felt optimistic but currently faced challenges that they found difficult to overcome especially with regard to persistent xenophobia.